(untitled) (Indian Journal of Public Health Research & Development, 2020)
Assessment of risk of fall among elderly in selected community area, Kanchipuram district, Tamilnadu, India. The objectives are to assess the risk of fall among elderly in selected community area, To associate the risk of fall with demographic variables in selected community area. The resrarch approach used for the study was Quantitative Approach Purposive sampling technique was used to select 60 samples. The data were collected by using Fall Risk Assessment scale. The collected data were tabulated and analyzed. The level of significance selected was p<0.05 level. Descriptive and inferential statistics were used. The result showed that 62% of elderly had low level of risk where as 38% of elderly had moderate level of risk of fall. the showed that the demographic characteristics like Age (?2 -7.588), Blood Pressure (?2 - 2.00), Diabetes (?2 - 2.347), Vision (?2 - 3.45)have significant association where as demographic characteristics like Gender ?2 - (0.020), Arthritis (?2 - 0.006) have no significant association .